Detection of pepsin and IL-8 in saliva of adult asthmatic patients - Marshall, Samuel (J Asthma Allergy, 2019)
Objective: Asthma and gastric reflux disease are widespread and often coexisting diseases with complex interactions, leading some to suspect that asthma symptoms of patients with reflux may improve with anti-reflux therapy. The objective of this study was to determine whether pepsin in saliva, indicative of airway reflux, could be detected in patients with asthma of varying severity and test the requirement of citric acid as a pepsin preservative. Methods: Saliva samples were collected in the clinic (with/without citric acid) and upon waking the following morning from 25 asthmatic patients. Enzyme-linked immunosorbent assay was performed for pepsin and interleukin-8 (IL-8), an inflammatory cytokine induced by pepsin in other airway epithelia. Pepsin induction of IL-8 was tested in a lung epithelial cell culture model. Results: Pepsin was detected in saliva from 14/25 patients (56%; mean concentration of pepsin in specimens where observed ±SD =80.3±87.5 ng/mL); significant agreement was found between samples collected in the presence/absence of citric acid. No significant associations were found with pepsin and clinical measures of asthma severity. IL-8 was detected in saliva from 22/25 patients (88%; mean IL-8 in all specimens where observed =3.27±3.91 ng/mL). IL-8 was significantly upregulated in human lung epithelial cells exposed to pepsin at pH7 in vitro (P=0.041). Conclusion: In summary, more than half of the asthma patients in this study were found to have pepsin in their saliva, indicative of airway reflux. These data support the use of salivary pepsin as a noninvasive tool for future investigation of airway reflux in a larger cohort. The data further suggest that collection in citric acid as a sample preservative is not warranted and that pooling of multiple saliva samples collected at various timepoints may improve sensitivity of pepsin detection and reduce costs incurred by multiple sample analysis in future studies.